2019
DOI: 10.1017/s000711451900285x
|View full text |Cite
|
Sign up to set email alerts
|

Konjac glucomannan polysaccharide and inulin oligosaccharide enhance the colonic mucosal barrier function and modulate gut-associated lymphoid tissue immunity in C57BL/6J mice

Abstract: Both konjac glucomannan (KGM) and inulin oligosaccharide have been shown to improve bowel function, but their effects on the mucosal barrier function and immunity are not fully understood. The aim of the present study was to determine the effects of a low-level supplementation of dietary fibres on the colonic mucosal barrier function, antioxidant enzyme defence and immunity. C57BL/6J mice (6 weeks of age, eight per group) were randomly assigned to consume one of the following diets: control or control diet sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…The intestinal mucus layer is constantly replenished via the secretory activity of goblet cells . Although both KGM and KGM oligosaccharides have been reported with protective effects on the colonic mucus layer, ,, the molecular mechanism for this is mostly unclear. To gain better insights into the effects of KGM oligosaccharides on intestinal function and provide a reference for related studies in vivo, the intestinal architectural changes upon KGMOS treatment were investigated.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intestinal mucus layer is constantly replenished via the secretory activity of goblet cells . Although both KGM and KGM oligosaccharides have been reported with protective effects on the colonic mucus layer, ,, the molecular mechanism for this is mostly unclear. To gain better insights into the effects of KGM oligosaccharides on intestinal function and provide a reference for related studies in vivo, the intestinal architectural changes upon KGMOS treatment were investigated.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Short-chain fatty acids extracted from colonic fecal samples by diethyl ether were determined using a gas chromatograph (GC-2014, Shimadzu, Kyoto, Japan) connected with a glass capillary column and a flame ionization detector as reported previously …”
Section: Methodsmentioning
confidence: 99%
“…27 Furthermore, supplementation of sufficient KGM could enhance the mucosal barrier function and anti-inflammatory status. 28 In recent years, emerging evidence has suggested that dietary fiber could noticeably attenuate constipation by modulating the expression of aquaporin. 29 However, this study might provide instructive reference for the comparative study of promoting gastrointestinal motility, mucous secretion, and gut probiotic microbiota, except for the mechanisms of regulating liquid water metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Hemicelluloses such as popular glucomannan (also called ‘konjac’) are usually considered prebiotics [ 16 ] as they both undergo hydrophilic decomposition and are easily transported to the distal gut [ 17 ] for microbial fermentation [ 18 ]. Native konjac glucomannan has limited uses and has been chemically/physically/enzymatically modified to expand the range of functional properties, including biodegradable film, medical and pharmaceutical material, and encapsulation [ 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%